2017
DOI: 10.1210/en.2017-00636
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Processing of Prohormones in Secretogranin III–Null Mice Causes Maladaptation to an Inadequate Diet and Stress

Abstract: Secretogranin III (SgIII), a member of the granin family, binds both to another granin, chromogranin A (CgA), and to a cholesterol-rich membrane that is destined for secretory granules (SGs). The knockdown of SgIII in adrenocorticotropic hormone (ACTH)-producing AtT-20 cells largely impairs the regulated secretion of CgA and ACTH. To clarify the physiological roles of SgIII in vivo, we analyzed hormone secretion and SG biogenesis in newly established SgIII-knockout (KO) mice. Although the SgIII-KO mice were vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…Notably, the SCG3-CPE interaction helps this prohormone processing [17]. In line with this concept, previous studies indicated that SCG3 had some roles in assisting the formation of insulin-containing secretory granules and insulin processing, thus affecting glucose homeostasis [18,19]. In our study, serum SCG3 concentrations were positively related to FPG, glycated hemoglobin, and glucose levels at two hours of the OGTT.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Notably, the SCG3-CPE interaction helps this prohormone processing [17]. In line with this concept, previous studies indicated that SCG3 had some roles in assisting the formation of insulin-containing secretory granules and insulin processing, thus affecting glucose homeostasis [18,19]. In our study, serum SCG3 concentrations were positively related to FPG, glycated hemoglobin, and glucose levels at two hours of the OGTT.…”
Section: Discussionsupporting
confidence: 82%
“…Acting as a bridge of peptides and a trans-Golgi network, it sorts these prohormones into secretory granules [16,17]. As for insulin secretion, SCG3 also had some roles in assisting insulin processing, thus affecting glucose homeostasis [18,19]. It has been shown that significantly increased SCG3 levels were detected in serum-free media conditioned with non-responsive high-passage MIN-6 cells, a model of dysfunctional beta cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCG3 is a member of the granin family found in various endocrine and neuroendocrine cells [29,30,31]. It affects glucose homeostasis by regulating insulin secretion from pancreatic β-cells [32,33]. MetS is characterized by compensatory hyperinsulinemia and insulin resistance [34,35].…”
mentioning
confidence: 99%